Compensation Management and Canadian Wrongful Dismissal: Lessons from Litigation - McShane, Steven; Redekop, Bruce (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
This paper analyzed 110 recent Canadian common law wrongful dismissal cases to identify principles pertaining to compensation management policies and practices. All of these cases involve «constructive dismissal», where the employee sues the employer for altering a fundamental condition of employment (other than outright termination). The case law has been divided into four general headings: pay level issues, payform issues, pay structure issues, and pay communication issues.